2014
DOI: 10.26719/2014.20.10.605
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for hepatitis B and C virus infection in Damietta Governorate, Egypt

Abstract: Hepatitis B and C virus (HBV and HCV) infections remain major public health problems in Egypt and data are needed on risk factors for infection. This study determined the prevalence of anti-HCV and HBV surface antigen seropositivity in Damietta Governorate, Egypt, and evaluated potential risk factors for infection and the impact of HBV vaccination on seroprevalence. A household, cross-sectional study was conducted of 2977 individuals. About 20% were vaccinated against HBV. Only 1.1% were infected with HBV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
3
16
1
Order By: Relevance
“…Main risk factors for both hepatitis C virus and HBV were exposure to dental procedures and surgery in one study. 32 Although in other studies, 33,34 reuse of razor blades and needle-stick injuries have been documented as risk factors for HBV infection, we did not find this so in our study. In yet another study, risk factors such as unprotected sex, mouth-to-mouth kissing, blood transfusion, public barbing salon clipper cuts, manicure and pedicure cuts, and scarification were not significantly associated with the presence of HBsAg.…”
Section: Resultscontrasting
confidence: 82%
“…Main risk factors for both hepatitis C virus and HBV were exposure to dental procedures and surgery in one study. 32 Although in other studies, 33,34 reuse of razor blades and needle-stick injuries have been documented as risk factors for HBV infection, we did not find this so in our study. In yet another study, risk factors such as unprotected sex, mouth-to-mouth kissing, blood transfusion, public barbing salon clipper cuts, manicure and pedicure cuts, and scarification were not significantly associated with the presence of HBsAg.…”
Section: Resultscontrasting
confidence: 82%
“…In a study published in 1985, prevalence of HBsAg among residents of two Egyptian provinces was as high as 10.1 % with anti-HBc found in 88 % [37]. More recent data suggests intermediate endemicity levels [38,39], and even low (<2 %) prevalence has been reported among blood donors [40,41]. In Pakistan, the overall prevalence of HBV has been estimated to 4.3 %, though higher prevalence rates were shown in specific sub-populations such as multi-transfused (6.2 %), surgical patients (7.4 %), and IDUs (15 %) [42].…”
Section: Eastern Mediterraneanmentioning
confidence: 91%
“…Furthermore, a house-hold survey done in Damietta, Egypt, 2014, found that 1.1% of the participants were infected with HBV, 9.3% with HCV, and both infections co-existed in 0.4%. One of the main risk factors for both infections was exposure to dental procedures [11]. In addition, the continuous increase in the number of patients seeking dental clinics should give alarming signs to dentists and Dental Health Care Programs (DHCPs) for better awareness of extra-precautions required while treating the dental patients.…”
Section: Introductionmentioning
confidence: 99%